Analisis Potensi Wilayah dalam Pemanfaatan Bonus Demografi - Asnidar Asnidar; Fara Labita; Nurlaila Hanum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the potential of the region in utilizing the demographic bonus in Aceh Tamiang Regency. The data used in this study is the PDRB data of Aceh Tamiang Regency and Aceh Province in 2019-2023. The data analysis method uses location question (LQ) and shift share analysis. Based on the results of the LQ analysis, it is known that there are 4 (four) business fields that can become leading sectors in Aceh Tamiang Regency and at the same time are the economic base for further development, namely the agriculture, forestry, and fisheries sectors; mining and quarrying; processing industry; and other services. Meanwhile, based on the shift share analysis, it can be seen that the sectors that have a positive impact on the utilization of the demographic bonus in Aceh Tamiang Regency are the wholesale and retail trade sector, car and motorcycle repairs. In addition to providing a good contribution to the utilization of the demographic bonus in Aceh Tamiang Regency and can increase the PDRB of Aceh Province.